Analisis Cerita Nabi Muhammad SAW dalam Mengembangkan Kepekaan Sosial Anak Usia Dini - Anisatul Fuadah; Raden Rachmy Diana (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2025)
The phenomenon of violence and decreased social sensitivity in children in the modern era is a serious problem that requires an educational approach from an early age. This study aims to analyze the potential of the Prophet Muhammad's stories as a medium in developing social sensitivity in early childhood and to design the basis for developing an applicable character learning model. Using the literature study method, this research analyzes three main stories: the Prophet's interaction with Abu Umair and his pet bird, his silent help to a Jewish beggar who was hostile to him, and his patient attitude towards a neighbor who often hurt him. The three stories reflect universal values such as empathy, patience, tolerance, consistency in doing good, and the ability to repay bad with good. These values are considered very relevant for children's character building and can be implemented in an integrated manner through the involvement of teachers, parents and the surrounding environment. The results show that the Prophet's story not only functions as a means of conveying moral messages, but also has transformative power in shaping children's social sensitivity in a sustainable manner.